Factors affecting to the employee satisfaction in textile industries: An empirical study based on thulhiriya boi area - Godagampala, G.D.N.M. (University of Jaffna, 2020)
Employee satisfaction has always been an important issue for organizations. Employees are viewed as the greatest strengths and resources of an organization. An organization’s success depends on the employees and thus, they should not be deprived of what they deserve in return for their commitment to the organization. The employees of an organization must derive a good amount of satisfaction from the job. However, very few organizations have made employee satisfaction a top priority, perhaps because they fail to understand the significant opportunity that lies in front of them. Many organizations fail to understand the basic meaning of employee satisfaction. Employee satisfaction is more of an attitude – an internal state. The previous studies had identified factors affecting the job satisfaction of employees in the textile industry, excluding the factors of the working environment. Therefore, this study attempted to identify the factors affecting the employee job satisfaction of garment industries incorporating a specific area of working environment conditions of employees. This study was conducted using primary data collected from the Thulhiriya BOI area. Through the random sampling method total of 300 questionnaires were analyzed using Logit model and frequency tables. The findings indicate that variables Health Status, Service Period, Gender, Age of the employee and Wage level are significant variables to determine employee satisfaction in textile industries. In contrast, Education level, Amount of Incentives and Marital Status are insignificant variables to determine employee satisfaction. Based on frequency table analysis, we can conclude that employees are highly satisfied with the planning process, vocational training and their job performance while moderately satisfied with work, supervision and training. Also, they are dissatisfied with the payment scheme and team sprit with co-workers. Results indicate that both employee-oriented and Work environment factors are essential to determine job satisfaction of employees in textile industries. It is supposing that the conclusions of this research can be used in all textile garments in Sri Lanka to identify the most important factors affecting to the job satisfaction of employees in garment industries. It will help to promote the programs that are useful to encourage the performance of employees for the target of company success.
Keywords: Job satisfaction; Logit model and organization